COMPOSITION OF GILLNET CAPTURE RESULTS IN NIPAH PANJANG 1 TANJUNG JABUNG TIMURDISTRICT JAMBI PROVINCE - Yosua Rivaldo Lumbantoruan; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in January 2018 at PPI Kelurahan Nipah Panjang 1 East Tanjung Jabung Regency. The purpose of this research is to know the comparison of catching gillnet fishing equipment in the morning and night time as well as the physics, chemical and biological parameters in Nipah Panjang waters. The method used is survey method. Data processing with t-test and analyzed descriptively. The catch during the study was 1526 kg or 3977 tails. Type of fish caught is baung laut (Macrone nemurus V) 34.50%, senangin (Polynemus tetrdactylus)34.44%, sembilang (Paraplotosusu albilabris)15.79%, lidah (Cynoglossus lingua ) 4.78%, shark (Charcharias falciformes ) 3.60%, biang (Setipinna melanochir) 1.64% and gulamah (Pseudocienna amovensis) 5.24%. The result of measurement of environmental parameters during the research is the current velocity ranged from 0.1 to 0.3 m / s, the temperature in the morning ranges from 28-30 0C, while the night ranges from 29-31 0C, the water brightness ranges between 55-60 cm, salinity range between 25 - 28 ‰, into the tidal range of 2.5-3 m while the tide ranges from 1 to 1.5 m. The result of t-test concludes the morning and night catch both by the number of fish and the weight of the caught fish is significantly different. Keyword: Nipah Panjang 1, gillnet, catch, environmental parameters